2019
DOI: 10.3389/fimmu.2019.01310
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretch Force Induces Periodontal Ligament Cells to Secrete Exosomes That Suppress IL-1β Production Through the Inhibition of the NF-κB Signaling Pathway in Macrophages

Abstract: In the oral mechanical environment, periodontal ligament cells (PDL cells) contribute to maintaining periodontal tissue homeostasis. Recent studies showed that exosomes, which are small vesicles secreted by various types of cells, play a pivotal role in cell-to-cell communication in biological processes. We examined the secretion of exosomes from PDL cells stimulated with cyclic stretch and their role in the inflammatory response of macrophages using the human macrophage cell line THP-1 and human primary monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 61 publications
1
76
0
Order By: Relevance
“…Exosomes have been shown to function as a means of intercellular communication in the body. Exosomes from PDLSCs promote bone regeneration and revascularization [7], and exosomes released in mechanical environments contribute to the maintenance of periodontal immune/inflammatory homeostasis [8]. Osteocytes are also mechanically sensitive cells and can secrete multiple biologically active factors to regulate bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have been shown to function as a means of intercellular communication in the body. Exosomes from PDLSCs promote bone regeneration and revascularization [7], and exosomes released in mechanical environments contribute to the maintenance of periodontal immune/inflammatory homeostasis [8]. Osteocytes are also mechanically sensitive cells and can secrete multiple biologically active factors to regulate bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…The present study assessed the effects of FPS-ZM1 on HG-stimulated inflammation in BMSCs. It was previously observed that HG conditions promoted inflammatory factors and inflammatory cytokines, such as TNF-α, IL-1β and il-6, in periodontal tissues (46,47). The present study on BMScs presented similar findings; TNF-α, IL-1β and il-6 expression was enhanced after HG stimulation, whereas these effects were inhibited by FPS-ZM1.…”
Section: Discussionsupporting
confidence: 87%
“…110 In addition, exosomes from chondrocytes could Suppress IL-1β production via inhibiting NF-κB signaling pathway. 156 promote the chondrogenic differentiation of BMSCs by activating the Wnt/β-catenin pathway, which was related to the inhibition of GSK-3β expression by exosomal miR-8485. 111 These results supported that chondrocytes could produce exosomes that mediate cell-cell communication, which play a functional role in AC maintenance and OA pathogenesis.…”
Section: Exosomes In Oamentioning
confidence: 99%